Optimization of Seaplane Maintenance in Coastal Areas - Prayitno, Hadi; Bahrawi, Ahmad; Wulansari, Ajeng; Wicaksono, Putra (Journal of Research in Social Science and Humanities, 2025)
This research presents the optimization of seaplane maintenance in coastal areas, emphasizing the importance of qualitative research methods to understand the experiences and problem-solving approaches of maintenance personnel. This study highlights the unique operational challenges faced by seaplanes, particularly their susceptibility to corrosion in harsh environments. Regular inspections at specific intervals (25, 50, 100, and 200 flight hours) are critical to ensure the structural integrity and functionality of the flotation device. This research underscores the need for pilots and technicians to have basic maintenance knowledge to uphold airworthiness, especially during long-range operations, while addressing risks associated with environmental factors such as saltwater and ice.